Risk Assessment on Stroke by Using Framingham Score and the Correlation with Obesity and Profelipid on Bima Ethnic Group at Bima (International Journal of Studies in Nursing, 2019)
Stroke is an acute nerve function disorder which caused by the dysfunctional blood flow to the brain, the symptoms depend on the brain focal area that has dysfunctions. Stroke has become the fifth of the cause of death in the United States, kills nearly 130,000 people each year, 1 of 20 deaths is caused by stroke. In every 40 seconds in the United States, a person is afflicted by stroke. In every 4 minutes, two people died of stroke. Every year approximately 795,000 people in the United States have stroke. Among its 610,000 had stroke for the first time while the rest 185,000 people had their series of occurrence. Research design used in this research is cross sectional method that stresses on certain time data measurement. This research’s subject is patients of Health Clinic Center throughout Bima who participate in POLANIS program. The sampling method of this research is consecutive sampling, so the sampling choices are all individuals which comply to the sample criteria, until the designated sample number is reached. Framingham Score Sheet is used by the writer as the research instrument.The correlation test resulted in p value > 0.05 so it can be concluded there is no relationship between obesity by framingham score to incidents of stroke and also the correlation test resulted in p value > 0.05 and it can be concluded that there is no relationship between obesity by framingham score with the risk of stroke. There is no relevance between obesity and cholesterol by framingham score with the incidents of stroke and the risk of stroke for responders in Health Clinic Center throughout Bima.